What is Amphipteryx agrioides Selys 1853 (Odonata: Amphipterygidae)? - González-Soriano, Enrique; Von Ellenrieder, N. (Zootaxa, 2009)
The family Amphipterygidae comprises a group of moderately large, robust species of pan-tropical damselflies. It was first recognized by Selys (1853) as his "6me legion" based on the description of a unique female which he named "Amphipteryx agrioïdes." Its provenance ("Colombie. [Collect. Selys.]") has remained a mystery as no specimens of this genus had subsequently been collected from South America. Selys (1854a: 241, 243) expanded on the distribution of the specimen noting (page 241) that it had been collected “dans la province de Cumana (Amérique méridionale équatoriale)” and (page 243) “d’après un exemplaire recueilli par M. Funck, et qui se trouvait avec l’ Hetaerina majuscula et l’ Agrion (Hyponevra) Funcki….” De Marmels (1990) dismissed the record of A. agrioides from “Cumaná [Venezuela]” as unlikely and suggested deletion of the species from that country.The single holotype female was apparently never re-examined, except by the late B.E. Montgomery who never published his observations, until recently (von Ellenrieder & Garrison 2007). Calvert (1901) in his Biologia Centrali-Americana assigned this name to specimens from Mexico and Guatemala. He described the male for the first time and gave a description of the female comparing it with the original description and noting that "The hind prothoracic lobe also possesses two dorsal lamellate processes (not mentioned by Selys)…." González (1991) described A. longicaudatus (should be A. longicaudata; Novelo 1995) from Oaxaca, Mexico and distinguished this species from A. agrioides based only on Calvert's (1901) description and illustrations. Several years ago, Rosser W. Garrison was sent digital images of the holotype female of A. agrioides by Jérôme Constant of the IRSNB, and observed that the pronotal armature differed from specimens given this name by Calvert (1901) and González (1991) (Garrison pers. comm.). Since Amphipteryx is the type genus of the family Amphipterygidae, it is imperative that its type species, A. agrioides, be correctly assigned to specimens. The purpose of this paper is to determine the correct identity of A. agrioides, provide diagnostic illustrations of the same, and discuss the location of its type locality.